The Effect of Future Expectations, Pocket Money, and Sharia Financial Behavior on Halal Lifestyle: A Case Study of University Students in Medan City - Sari, Siska Kumala; Syahriza, Rahmi; Nurbaiti, Nurbaiti (LPPM Universitas Jambi, 2026)
This study seeks to investigate the impact of future aspirations, discretionary income, and Islamic financial practices on the embrace of a halal lifestyle among university students in Medan City. This study employs a quantitative technique with an associative research design. The sample consisted of 100 respondents, determined using the Slovin formula, with purposive sampling being the applied method. Data were collected through questionnaires and processed using multiple linear regression with SPSS software. The findings indicate that future ambitions, discretionary income, and Islamic financial practices have a favourable and significant impact on the adoption of a halal lifestyle. The Adjusted R Square value of 0.499 signifies that 49.9% of the variance in halal lifestyle is explained by the three independent variables in the model, while the remaining 50.1% is influenced by external factors not included in this study. The findings indicate that the halal lifestyle among university students in Medan City can be reinforced by fostering positive future expectations, managing pocket money effectively, and adopting Islamic financial behaviours consistent with Islamic principles. Consequently, a halal lifestyle reflects students’ awareness in applying sharia principles in both economic activities and daily life practices.